Dealer's perception towards aqua feeds-A case study of avanti feeds limited, Kovvur, West Godavari Dt. of Andhra Pradesh - GDV Kusuma; B Ravi Kumar; Murthy Chavali (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2020)
The first feed company was set up at Nellore district in Andhra Pradesh named as "Water Base" in the year 1992. The Indian aqua industry has collaborated with East Asian countries like Taiwan, Thailand etc. All the machinery and 83% of raw materials are imported from East Asian Countries. The R&D aspects are also imported from other countries but in India, the research and development departments are still underdeveloped. A sample of 200 dealers was taken for the purpose of this study with a structured questionnaire was drafted and distributed to dealers for collecting the primary data. Applying the theoretical models and the related statistical tools, the data collected by the researcher in the form of primary and secondary data, the hypothesis were tested and arrived at conclusions on the problem.